Competitive strategies among Ontario farms marketing direct to consumers - Eric T. Micheels; Andreas Boecker (Agricultural and Food Economics, 2017)
This paper examines the importance of two resources, namely a market orientation and an entrepreneurial orientation, in new product development and satisfaction with firm performance among direct and alternative marketers. Using a partial least squares structural equation model and data from a 2013 survey, this paper models the effect of a market orientation and entrepreneurial orientation on satisfaction with current performance and expected future performance for agricultural firms in Ontario, Canada. Our results show that a market orientation and entrepreneurial orientation are important factors in determining rates of product and marketing innovations among farm-based agribusinesses. These findings further demonstrate that a market orientation is a powerful resource as it enables firms to become aware of opportunities to provide superior value for consumers, especially when operating in non-traditional markets.
Keywords: D22; D83; M31; M37; 330; Direct marketing; Entrepreneurial orientation; Market orientation; Marketing innovation; Product innovation